The “Alluvial Mesovoid Shallow Substratum”, a New Subterranean Habitat - Ortuño, Vicente M. (Public Library of Science, 2013)
In this paper we describe a new type of subterranean habitat associated with dry watercourses in the Eastern Iberian Peninsula, the “Alluvial Mesovoid Shallow Substratum” (alluvial MSS). Historical observations and data from field sampling specially designed to study MSS fauna in the streambeds of temporary watercourses support the description of this new habitat. To conduct the sampling, 16 subterranean sampling devices were placed in a region of Eastern Spain. The traps were operated for 12 months and temperature and relative humidity data were recorded to characterise the habitat. A large number of species was captured, many of which belonged to the arthropod group, with marked hygrophilous, geophilic, lucifugous and mesothermal habits. In addition, there was also a substantial number of species showing markedly ripicolous traits. The results confirm that the network of spaces which forms in alluvial deposits of temporary watercourses merits the category of habitat, and here we propose the name of “alluvial MSS”. The “alluvial MSS” may be covered or not by a layer of soil, is extremely damp, provides a buffer against above ground temperatures and is aphotic. In addition, compared to other types of MSS, it is a very unstable habitat. It is possible that the “alluvial MSS” may be found in other areas of the world with strongly seasonal climatic regimes, and could play an important role as a biogeographic corridor and as a refuge from climatic changes.